Another look at the determinants of current account imbalances in the European Union: An empirical assessment - Agnieszka Gehringer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2012)
In a dynamic panel framework, I investigate the qualitative aspects of factors determining current account imbalances in (country groupings within) the European Union. I consider the standard determinants of current account positions discussed in the past literature, but additionally, I include a series of explanatory variables that refer to the sectoral composition of the European economies and that could have significantly contributed to the current account developments in the past decades. Independently of the econometric method used, the main finding suggests that the economic predominance of the construction sector might have played an important role in aggravating current account positions in the European economies. In parallel, some negative influence could be found for some other service sectors, but this shouldn't be of much concern due to their role played in the growth process.
Keywords: F32; F34; F36; 330; current account determinants; construction sector; European Union; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Bauwirtschaft; EU-Staaten